Active galactic nuclei from He ii: a more complete census of AGN in SDSS galaxies yields a new population of low-luminosity AGN in highly star-forming galaxies. Issue 3 (17th December 2016) - Bär, Rudolf E.; Weigel, Anna K.; Sartori, Lia F.; Oh, Kyuseok; Koss, Michael; Schawinski, Kevin
Abstract: In order to perform a more complete census of active galactic nuclei (AGN) in the local Universe, we investigate the use of the He ii λ4685 emission line diagnostic diagram by Shirazi & Brinchmann (2012 ) in addition to the standard methods based on other optical emission lines. The He ii -based diagnostics is more sensitive to AGN ionization in the presence of strong star formation than conventional line diagnostics. We survey a magnitude-limited sample of 63 915 galaxies from the Sloan Digital Sky Survey Data Release 7 at 0.02 <  z  < 0.05 and use both the conventional BPT emission line diagnostic diagrams, as well as the He ii diagram to identify AGN. In this sample, 1075 galaxies are selected as AGN using the BPT diagram, while additional 234 galaxies are identified as AGN using the He ii diagnostic diagram, representing a 22 per cent increase of AGN in the parent galaxy sample. We explore the host galaxy properties of these new He ii -selected AGN candidates and find that they are most common in star-forming galaxies on the blue cloud and on the main sequence where ionization from star formation is most likely to mask AGN emission in the BPT lines. We note in particular a high He ii AGN fraction in galaxies above the high-mass end of the main sequence where quenching is expected to occur. We use archival Chandra observations to confirm the AGN nature of candidates selected through He ii -based diagnostic. Finally, we discuss how this technique can help inform galaxy/black hole coevolution scenarios.